3D game textures : create professional game art using Photoshop - Ahearn, Luke, ....- (Amsterdam ; Boston : Focal Press/Elsevier, 2012)
A broadly enhanced new edition of Luke Ahearn's cornerstone game art book "3D Game Textures" is here. When digital art software was in its infancy, most digital art, especially vector art, was textureless. With the advance in software, it is now possible to incorporate texture into most types of digital art. However, if the artists cannot build their own textures, they are limited to using commercial textures. In this enhanced 3rd edition of Luke Ahearn's gem of a book, not only does Luke teach you how to create your own unique textures, he also teaches how to create shaders (the visual effects - reflections, refractions, opacity - that make textures come to life) and materials (collections of shaders that fill well together to map to a particular scene or environment). You can now expand your skill set immeasurably, and create more compelling, varied art work from scratch.
Machine generated contents note: Introduction Textures Art Theory Breaking the world down visually Recreating the world visually in Photoshop Art as applied to CG applications Shaders and Materials Shader vs. Material What is a material system Nodes Node Input Node types and functions Material Examples Diffuse Specular Ambient Reflection real and faked Refraction Transparency Bump/ Displacement/ Normal mapping Specialized Materials; Skin etc. Creating Complex Materials Metals Glass Wood Compound Materials.
Includes index.
Keywords: Computer games -- Programming; Computer graphics; Adobe Photoshop